Dissecting Hierarchies between Light, Sugar and Auxin Action Underpinning Root and Root Hair Growth - García-González, Judith; Lacek, Jozef; Retzer, Katarzyna (Plants (Basel, Switzerland), 2021)
Plant roots are very plastic and can adjust their tissue organization and cell appearance during abiotic stress responses. Previous studies showed that direct root illumination and sugar supplementation mask root growth phenotypes and traits. Sugar and light signaling where further connected to changes in auxin biosynthesis and distribution along the root. Auxin signaling underpins almost all processes involved in the establishment of root traits, including total root length, gravitropic growth, root hair initiation and elongation. Root hair plasticity allows maximized nutrient uptake and therefore plant productivity, and root hair priming and elongation require proper auxin availability. In the presence of sucrose in the growth medium, root hair emergence is partially rescued, but the full potential of root hair elongation is lost. With our work we describe a combinatory study showing to which extent light and sucrose are antagonistically influencing root length, but additively affecting root hair emergence and elongation. Furthermore, we investigated the impact of the loss of PIN-FORMED2, an auxin efflux carrier mediating shootward auxin transporter, on the establishment of root traits in combination with all growth conditions.
Keywords: sugar; shootward auxin transport; root hair elongation; sucrose; root hair; light grown roots; root growth; dark grown roots; total root length; gravitropic index; PIN-FORMED2